Early Introduction of Food Allergens and Risk of Developing Food Allergy - Yakaboski, Elizabeth (Nutrients, 2021)
There is increasing evidence that early introduction of allergenic foods may decrease the risk of developing IgE-mediated food allergy. Patterns of food introduction before the 2015 publication of the Learning Early about Peanut Allergy (LEAP) trial are not well-studied, but are important as a baseline for evaluating subsequent changes in infant feeding practices and potentially food allergy. We performed a retrospective longitudinal study using data from a multicenter cohort of infants hospitalized with bronchiolitis between 2011–2014. The primary outcomes were IgE-mediated egg or peanut allergy by age 3 years. Of 770 participants included in the analysis, 635 (82%) introduced egg, and 221 (27%) introduced peanut by age 12 months per parent report. Four participants had likely egg allergy, and eight participants had likely peanut allergy by age 3 years. Regular infant egg consumption was associated with less egg allergy. The association was suggestive for infant peanut consumption with zero peanut allergy cases. Overall, our results suggest that early introduction of peanut was uncommon before 2015. Although limited by the small number of allergy cases, our results suggest that early introduction of egg and peanut are associated with a decreased risk of developing food allergy, and support recent changes in practice guidelines.